العمارة الإسلامية بين الثوابت الحضارية والتأثيرات الخارجية: دراسة تحليلية في الأبعاد البيئية والاجتماعية والتاريخية - Tribak, Mohamed (Darul Yasin Al Sys, 2025)
This study investigates Islamic architecture as an integrated civilizational product shaped by a complex interplay of religious, social, political, economic, and environmental factors. The significance of the research lies in highlighting the distinctiveness of Islamic architecture, which is not merely a stylistic or aesthetic accumulation, but a powerful reflection of the Muslim Ummah's identity and interaction with its context. The study aims to analyze how these factors have contributed to the formation of a unique architectural language and to assess the extent of influence from prior civilizations such as the Roman and Byzantine, without compromising Islamic values. The central research question explores whether Islamic architecture can authentically represent the Muslim identity and whether it can serve as a foundation for contemporary architectural practices. Using an analytical and critical methodology, the study examines architectural models in their respective contexts. The findings show that Islamic architecture embodies a balanced civilizational awareness, combining functionality and beauty, and offering environmentally conscious and value-driven alternatives for modern architectural development.